JOURNEY OF FAITH: BIBLICAL ECCLESIAL TRAJECTORY - Xavier, Joseph (Asian Horizons, 2012)
Revelation and faith are two fundamental concepts of Christianity and its teaching. Christian theology is built on these foundational elements. According to the classical definition of St Anselm, theology is fides quaerens intellectum, faith seeking understanding. From that perspective, theology originates in the desire for deepening one’s faith. Pope Benedict in his Apostolic Letter, Porta Fidei, invites us to deepen our understanding of the gift of faith. Announcing the Year of Faith, the Pope writes: “We want to celebrate this Year in a worthy and fruitful manner. Reflection on the faith will have to be intensified, so as to help all believers in Christ to acquire a more conscious and vigorous adherence to the Gospel, especially at a time of profound change such as humanity is currently experiencing.”